Review-Localized High-Concentration Electrolytes for Lithium Batteries - Cao, Xia; Jia, Hao; Xu, Wu; Zhang, Ji-Guang (Journal of the Electrochemical Society, 2021)
The conventional LiPF6/carbonate-based electrolytes have been widely used in graphite (Gr)-based lithium (Li) ion batteries (LIBs) for more than 30 years because a stable solid electrolyte interphase (SEI) layer forms on the graphite surface and enables its long-term cycling stability. However, few of these electrolytes are stable under the more stringent conditions needed with a Li metal anode (LMA) and other anodes, such as silicon (Si), which exhibit large volume changes during charge/discharge processes. Many different approaches have been developed lately to stabilize Li metal batteries (LMBs) and Si-based LIBs. From this aspect, localized high-concentration electrolytes (LHCEs) have unique advantages: not only are they stable in a wide electrochemical window, they can also form stable SEI layers on LMA and Si anode surfaces to enable their long-term cycling stability. The ultrathin SEI layer formed on a Gr anode can also improve the safety and high-rate operation of conventional LIBs. In this paper, we give a brief summary of our recent work on LHCEs, including their design principle and applications in both LMBs and LIBs. A perspective on the future development of LHCEs is also discussed.